Measurement and analysis of the impact of oil shocks on fiscal policy - Isam Abdul Khudhur Saud, Esraa Said Saleh, Ali Mahdi Abbas Albairmani, (Opción, 2020)
Oil shocks directly affect fiscal policy in Iraq as a result of public budget dependence on oil revenues. Thus, Fiscal policy responds through its spending and revenue instruments in a way that is in line with or against the direction of oil shock. This research is about measurement and analyzing the response of fiscal policy towards oil shocks in Iraqi economy for period 2003-2017.